Pulmonary hemorrhage in patients receiving anti-platelets- a case series and a suggested therapeutic algorithm. (2022) - Tomos, Ioannis; Kallieri, Maria; Papaioannou, Andriana I.; Stagaki, Eleni; Raptakis, Thomas; Karakatsani, Anna; Korkonikitas, Panagiotis; Manali, Effrosyni D.; Karageorgou, Vagia; Mplizou, Myrto; Vlami, Katerina; Loukides, Stelios; et al.
Abstract: Antiplatelet therapy including aspirin and thienopyridine agents (such as clopidogrel, prasugrel and ticagrelor) are often used in patients with coronary disease. Pulmonary hemorrhage due to antiplatelet therapy although very rare, when excessive, is a life-threatening event. So far, there is lack of specific guidelines for the management of these patients. We report a case series of 5 patients receiving antiplatelet therapy who were admitted to the hospital due to pulmonary hemorrhage related to antiplatelet therapy. We also propose an algorithm on the management of these patients taking into consideration the balance between thrombotic and bleeding risk and the severity of the hemorrhage.